A critical review of Dunbar's social brain hypothesis - Acedo-Carmona, Cristina; Gomila Benejam, Antoni (Instituto de Estudios Sociales Avanzados (IESA-CSIC), 2016)
Dunbar’s social brain hypothesis constitutes an influential position among those that relate the evolution of human cognition and sociality. In this work, we first present the essentials of the theory and discuss the paleoanthropological and social evidence claimed to support it. We also point out its shortcomings, which have to do with the general strategy of finding linear relations among different traits, the lack of attention to the mental capacities that make human social life possible, and the diversity of social relations and structures that take place. We put forward our way of complementing Dunbar’s approach by focusing on the role of trust in cementing society and explaining diversity.
Una revisión crítica de la hipótesis del cerebro social de Dunbar
Keywords: Edad e inteligencia; Cerebro; Cognition; Evolution; Group; Neocortex; Sociality